2022
DOI: 10.2217/cns-2022-0004
|View full text |Cite
|
Sign up to set email alerts
|

Systemic inflammatory biomarkers in primary central nervous system lymphoma versus high-grade glioma: exploratory, comparative and correlative analysis

Abstract: Aim: To assess systemic inflammatory biomarkers in non invasive differential diagnosis of primary central nervous system lymphoma (PCNSL) from high-grade glioma (HGG). Materials & methods: Patients with similar morphology (PCNSL or HGG) on conventional neuro-imaging were included. Systemic inflammatory indices were calculated from pretreatment complete blood counts and liver function tests and compared against histopathology as reference standard. Results: Mean values of absolute lymphocyte count and progn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…Therefore, it is reasonable that PNI might have considerable prognostic value in PCNSL patients. Tejpal et al [ 34 ] found that the mean PNI significantly differed between patients with PCNSL ( n = 42) and high-grade glioma ( n = 16). A retrospective PCNSL study reported an association between the PNI and OS in the univariate analysis ( p = 0.004) but not the multivariate analysis [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is reasonable that PNI might have considerable prognostic value in PCNSL patients. Tejpal et al [ 34 ] found that the mean PNI significantly differed between patients with PCNSL ( n = 42) and high-grade glioma ( n = 16). A retrospective PCNSL study reported an association between the PNI and OS in the univariate analysis ( p = 0.004) but not the multivariate analysis [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, it has been gradually adopted as an prognostic indicator in multiple malignancies, including gynecological tumors and lung cancer, and it is increasingly being used to predict prognosis in other non-tumor diseases, including fractures, heart failure, and brain infarction [24]. Tejpal et al [25] found that the mean PNI signi cantly differed between patients with PCNSL (n = 42) and high-grade glioma (n = 16). A retrospective PCNSL study reported an association between the PNI and OS in the univariate analysis (p = 0.004) but not the multivariate analysis [16].…”
Section: Discussionmentioning
confidence: 99%